The remarkable activity and stability of a dye-sensitized single molecular layer MoS2 ensemble for photocatalytic hydrogen production. Issue 70 (27th July 2015) - Jia, Tiantian; Li, Molly M. J.; Ye, Lin; Wiseman, Sam; Liu, Guoliang; Qu, Jin; Nakagawa, Keizo; Tsang, S. C. Edman
Abstract : Single layer MoS2 synthesized by exfoliation with Li is demonstrated to take up the dye molecule, Eosin Y, with strong binding affinity via sulfur vacancies. Abstract : Single layer MoS2 synthesized by exfoliation with Li is demonstrated to take up the dye molecule, Eosin Y, with strong binding affinity via sulfur vacancies. This dye-sensitized single layer MoS2 ensemble exhibits remarkable activity and stability for photocatalytic hydrogen production from water.